Penerapan Hukum Bisnis Sebagai Upaya Menstimulus Kinerja Umkm Dalam Perspektif Marketing - Tubagus Dicky Faldy Syahid Noor; Yulia Nurendah; Weman Suardy (Jurnal Abdimas Dedikasi Kesatuan, 2021)
Micro, Small, and Medium Enterprises are business activities that are able to expand employment opportunities and provide broad economic services to the community, and can play a role in the process of equity and increase people's income, encourage economic growth and play a role in realizing national stability. MSMEs need knowledge related to the legalization of designs, packaging, for example the procedures for registering products for Trademarks, Copyrights, Industrial Designs and brand disputes. Keywords: Legality, Micro, Small, and Medium Enterprises, SWOT